Participatory Administration Affecting the Effectiveness of Sueksa Songkhro School under Special Education Bureau in the Northeast - Rattanathip, Juthamath; Piampuechana, Niyada (Dhammathas Academic Journal, 2022)
The purpose of this research are: 1) to study participatory administration and the effectiveness of Sueksa Songkhro school, 2) to study the relationship between participatory administration and 3) to study the predictor of participatory administration affecting the effectiveness. The sample groups used in this study were school administrators and teachers of Sueksa Songkhro school under Special Education Bureau in the Northeast region with of 232 people. The statistics used to analyze data comprised frequency, percentage, mean, standard deviation, Pearson Product-Moment Correlation and Stepwise Multiple Regression Analysis. The research result finds that: 1. Participatory Administration and the Effectivenesseach aspect was rated at a high level. 2. The relationship between participatory administration of school was positive correlated at a high level with statistical significance at the .01 level. 3. Participatory Administration the effectiveness of school was found that 2 variables were statistically significant at the .01 level.